DESIGN OF PRIVATE CLOUD STORAGE USING SECURITY METHODS IDS AND IPS - Deval Gusrion; Silky Safira; Retno Devita; Ruri Hartika Zain; Rini Sovia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Cloud computing is a form of technological progress that has developed along with the times, this has spurred the increasing use of the internet. By usingtechnology internet that is able to implement server a virtual, which has the aim of building a cloud computing server at the District Communications and Information Office. Padang Pariaman uses the Operating System (OS) Proxmox VE (Virtual Environment) 6.4. Cloud computing is able to provide storage services that can be used simultaneously. The results of this study produce a cloud computing server that implements a security system with themethods ids (intrusion detection system) and ips (intrusion prevention system)that are able to process data(storagestorage), use software simultaneously in the network, and use infrastructure within the scope of this research.network cloud computing at the District Communications and Information Office. Padang Pariaman using aservice model private cloud